PENGARUH KONSUMSI JUS BAYAM MERAH TERHADAP PENINGKATAN KADAR Hb PADA IBU HAMIL DI KECAMATAN TAWANGMANGU - Astuti, KH Endah Widhi; Widyastuti, Anik Hutari (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
The Government has sought to improve community nutrition, one of them  is the Anemia of Iron Nutritional especially suffered by pregnant women and women in general. The incidence of anemia in pregnant mothers in Indonesia reached 63.5%, whereas in Central Java in 2012 is estimated at 37.6% (Winonarianur, 2012). One source of  iron from plant materials are red spinach (amaranthus tricolor L). During this time the red spinach plant easily cultivated in Tawangmangu area but not many local people know the benefits as a source of iron. People still rely on chemical drugs to deal with and prevent anemia. To determine the effect of red spinach juice consumption to increase hemoglobin levels in pregnant women Trimester II in District Tawangmangu, to investigate the characteristics of respondents, to  know the hemoglobin level before consuming red spinach juice in the second trimester pregnant women, after one week of consuming red spinach juice and the second week after consuming red spinach. The method of this study was pre-experimental study design one group pretest-posttest. The population was all the second trimester pregnant women (14-28 weeks) as many as 128 people in the District Tawangmangu in August 2013. The sampling technique is purposive sampling. The sample in this study was the second trimester pregnant women who met the study criteria are as many as 20 responden. The average number hemoglobin levels before treatment is 11.210 g%, 1 week after treatment is 11.850 g%, and 2 weeks after treatment is 12.140 g%. The Increasing  levels of hemoglobin level in pregnant women who were given red spinach juice once daily for 2 consecutive weeks at an average of 0.93 g%. Test results analysis by Paired Sample T-Test values obtained significance (p) of 0.000. The predictive value of p <0.05. No significant effect giving red spinach juice once daily for 2 consecutive weeks in the second trimester pregnant women to increase hemoglobin levels. Keywords: red spinach, Haemoglobin